Pengaruh Penggunaan Learning Management System (LMS) Sevimaedlink Terhadap Kamandirian Belajar Dan Kemampuan Berfikir Kreatif - Hotim Hodijah, Putri Nur; Lestari, Wahyu; Djeni, Darwin (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
The use of the SEVIMA EdLink Learning Management System (LMS) aligns with the digital transformation in education and the Merdeka Curriculum. However, its application in mathematics learning to enhance students’ self-regulated learning and mathematical creative thinking skills remains empirically limited. This study aims to examine the effect of using SEVIMA EdLink LMS on the self-regulated learning and mathematical creative thinking abilities of Grade XI students at SMA U Zainul Hasan. This research employed a quantitative approach with a Pretest-Posttest Nonequivalent Control Group design. The sample consisted of two classes selected through purposive sampling: class XI F2A as the experimental group (using LMS) and class XI F2B as the control group (conventional learning). Data were collected through creative thinking tests and self-regulated learning questionnaires, then analyzed using t-tests and Pearson correlation at a significance level of 0.05. The results showed that the use of SEVIMA EdLink LMS significantly improved students' self-regulated learning and mathematical creative thinking abilities. Furthermore, a positive correlation was found between the two variables. These findings suggest that LMS can serve as an effective learning medium for improving the quality of mathematics education. Keywords: LMS Sevima Edlink, Self-Regulated Learning, Creative Thinking